GURU MENGINOVASI BAHAN AJAR SEBAGAI LANGKAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Siti Suprihatin; Yuni Mariani Manik (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Teachers are professions that require special expertise in their main tasks such as educating, teaching, guiding, directing, training, assessing and evaluating students in early childhood education in formal, primary and secondary education. Teachers apart from the assignment also design learning to help students in the learning process, so teachers need special expertise and high ability to develop teaching materials that are appropriate to the needs of students with the diversity of students' competence. The approach used in this research is qualitative with descriptive research type. Data collection is done by observation techniques and strengthened by theoretical studies from experts. Based on the data carried out by finding the learning process conducted by the teacher in class with teaching materials that have been developed by the teacher before the learning process takes place. Based on observations that the teaching material developed by the teacher has been able to provide convenience in students understanding the subject matter that the teacher conveys and the teaching material that the teacher has developed makes students eager to learn and solve the problems and problems the teacher provides, and is no less important than the development of teaching materials the teacher has made the learning outcomes obtained by students become visible from the results of the midterm exams of 32 students there are only 4 students whose grades are below the minimum graduation standard.